ANALYSIS OF STUDENTS’ READING COMPREHENSION LEVELS ON RECOUNT TEXT OF X GRADE STUDENTS AT SMA NEGERI 15 MEDAN - Lando Fortericho Sinurat; Nora Ronita Dewi (Universitas Negeri Medan, 2023)
The aim of this research is to find out the students’ reading comprehension proficiency in each levels of reading comprehension. This research was designed as a descriptive study. The data was obtained from the results of students’ answers to reading comprehension questions. The subjects of this study were the tenth grade students of SMA Negeri 15 Medan. The levels of reading comprehension were based on Barrett Taxonomy (Clymer, 1968). The results of this research showed that the students were properly proficient within the literal comprehension (98%), reorganization (95%), and inferential comprehension (82%). In contrast, the students struggled within the evaluation level (65%) and appreciation level (50%). Students were suggested to continue improving their reading comprehensy, most especially in the evaluation and appreciation level comprehension. Teachers were suggested to guide the students to connect with the text in a more personal and involving way to improve their proficiency in appreciation comprehension level.